COVID 19- Biochemical and Other Mechanisms associated with Neuropathy and Stroke. - Loung V Umedani; Quratulain Javaid (Gandhara University, 2024)
The Coronavirus (SARS-C0V-2) caused COVID 19 disease, commencing from China in December 2019 and soon in 2020 its neurological manifestations were noted. The viral spike (S) protein binding with host cell receptor angiotensin-converting enzyme 2 (ACE2) with assistance of membrane fusion protease (TMPRSS) caused viral entry in host cells. We searched 47 articles using PubMed from January 2021 to January 2023. The initial pooling of virus in nasal mucosa was followed by spread to respiratory and other tissues. This review highlights the neuropathy and stroke mechanisms. The role of receptors, enzymes, proteins and genes in neuropathological mechanisms are highlighted. Vascular endothelial effects, choroid plexus and Blood Brain Barrier disruptions were noted. The epigenetic neuropathological mechanisms need to be explored further to help in designing new therapeutic modalities. The post vaccination neurological manifestations as well as the post COVID effects both need further attention to promptly diagnose and start timely treatment.